LONG CHAIN POLYMERIC CARBOHYDRATE DEPENDENT NANOCOMPOSITES IN TISSUE ENGINEERING - Aslam, Muhammad Shahzad (Universal Journal of Pharmaceutical Research, 2020)
The use of nanomedicine has increased enormously, especially in the field of gene delivery and targeted drug delivery. The objective of current review to identify long-chain polymeric carbohydrate dependent nano-composites in tissue engineering such gellan gum incorporated TiO2 nanotubes, Poly(vinyl) alcohol-gellan gum-based nanofiber, cross-linked gellan/pva nanofibers, nanocellulose reinforced gellan-gum hydrogels, dextran and sol-gel derived bioactive glass-ceramic nanoparticles, aminated β-cyclodextrin-modified-carboxylated magnetic cobalt/nanocellulose composite, chitosan-chitin nanocrystal composite scaffolds, sodium alginate-xanthan gum-based nano-composite scaffolds, nano-hydroxyapatite pullulan/dextran polysaccharide composite, chitosan/carbon nanofibers scaffolds, nano-bio composite scaffold of chitosan–gelatin–alginate–hydroxyapatite, alginate/gelatin scaffolds with homogeneous nano apatite coating,nano-hydroxyapatite-alginate-gelatinmicrocapsule, poly(ε-caprolactone)/keratin nano fibrousmats, keratin nanoparticles-coating electrospun pva nanofiber, nano-hydroxyapatite/chitosan/chondroitin sulfate/hyaluronic acid and chitosan/chondroitin sulfate/nano-bioglass. The current review has identified a list of medicinal herbs that have been incorporated into long chain polymeric carbohydrate-based nano-composites. Peer Review History: Received 3 June 2020; Revised 7 July; Accepted 23 August; Available online 15 September 2020 Academic Editor: Essam Mohamed Eissa , Beni-Suef University, Egypt, dressamceutics@yahoo.com Reviewer(s) detail: Shahin Gavanji , World Academy of Medical Sciences, Iran, shahin.gavanji@khuisf.ac.ir Dr. Asia Selman Abdullah , University of Basrah, Iraq, asiaselman2016@gmail.com